2016
DOI: 10.3748/wjg.v22.i45.10071
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous dietary supplements:Garcinia cambogia-associated hepatic failure requiring transplantation

Abstract: Commercial dietary supplements are marketed as a panacea for the morbidly obese seeking sustainable weight-loss. Unfortunately, many claims cited by supplements are unsupported and inadequately regulated. Most concerning, however, are the associated harmful side effects, often unrecognized by consumers. Garcinia cambogia extract and Garcinia cambogia containing products are some of the most popular dietary supplements currently marketed for weight loss. Here, we report the first known case of fulminant hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 18 publications
1
51
0
Order By: Relevance
“…135 A 34-year-old Hispanic male required liver transplantation after the intake of G. cambogia 3 times a day. 136 A review article that was published in the same year listed G. cambogia among a list of dietary supplements that are hepatotoxic. 137 A 51-year-old female with a 12-year history of type 1 bipolar disorder started consuming G. cambogia and was easily irritated and agitated.…”
Section: Resultsmentioning
confidence: 99%
“…135 A 34-year-old Hispanic male required liver transplantation after the intake of G. cambogia 3 times a day. 136 A review article that was published in the same year listed G. cambogia among a list of dietary supplements that are hepatotoxic. 137 A 51-year-old female with a 12-year history of type 1 bipolar disorder started consuming G. cambogia and was easily irritated and agitated.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have described (hypo)mania and/or psychosis after the consumption of G. cambogia [ 87 , 119 , 120 , 121 ]. Some liver complications have also been reported, such as hepatotoxicity, with acute hepatic lesions, acute hepatitis, and hepatic insufficiency requiring transplant [ 122 , 123 , 124 , 125 ]. The complications from G. cambogia include mania or hypomania, mania with psychosis, and serotonin syndrome [ 10 , 126 ].…”
Section: Garcinia Species and Bioactive Compounmentioning
confidence: 99%
“…Lipidic peroxidation also increases oxidative stresss and can increase the risk of acute pancreatitis in patients using the species [ 131 ]. G. cambogia can cause other severe adverse events, including hepatoxicity and secondary acute hepatic insufficiency [ 124 , 132 ]. Other studies have also shown acute necrotizing eosinophilic myocarditis, rhabdomyolysis, serotonin toxicity, and nephropathy secondary to the use of G. cambogia [ 87 , 121 , 122 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ].…”
Section: Garcinia Species and Bioactive Compounmentioning
confidence: 99%
“…In one human trial, HCA has been supplemented with doses up to 5600 mg/day without adverse effects [168]. However, case reports have described severe hepatotoxicity, including acute liver failure requiring liver transplantation and acute necrotizing eosinophilic myocarditis in subjects using pure Garcinia cambogia supplements [169][170][171][172]. A natural product for weight loss containing Garcinia cambogia and a variety of other ingredients has been associated to fatigue, nausea, vomiting, colic, fever, chills, anorexia, abdominal pain, jaundice, increased levels of liver enzymes and bilirubin in healthy adults [173].…”
Section: Toxicity and Reactivitymentioning
confidence: 99%